Strategic adjustment between innovation and production: Generation of integrated archetypes in Spanish service firms - Dioni Elche Hortelano; Ángela Gonzáles Moreno (The University of Manchester, Manchester Business School, 2008)
This paper investigates empirically the strategic alignment between innovation and production strategies in a sample of service firms in Spain. It employs the integrated archetypes approach to analyse a dataset of unique, manually collected, firm responses. The results highlight differences in behaviour patterns underpinning both kinds of strategic decisions and, coherent with alignment theory, differential firm performance.
Keywords: 330; Marketingpolitik; Innovation; Performance-Messung; Dienstleistungssektor; Spanien